UI Design and Informative Usefulness in Influencing Gen Z's Purchase Intention: A Systematic Literature Review with Python-Based Analysis on the Mediating Role of Attention Span in TikTok In-Feed Videos - Nobel Sitohang; Ika Diyah Candra Arifah (Journal of Digital Business and Innovation Management, 2025)
This study presents a Systematic Literature Review (SLR) on the influence of UI design and informative usefulness on Gen Z's purchase intention, focusing on the mediating role of attention span within TikTok in-feed video advertisements. Using Python-based bibliometric and text mining tools, this review analyzes trends, research gaps, and theoretical frameworks in studies published from 2018 to 2024. Results show a significant correlation between engaging UI, valuable content, and short attention spans in driving purchase behaviors among Gen Z. The study identifies key factors influencing user interaction and suggests directions for future empirical research.